Survey of privacy preserving data queries in cloud computing - Ren-yi XIAO (Tongxin xuebao)
Driven by resource sharing,public clouds will become the national infrastructure like electricity grids and the Internet.A core issue in public cloud computing is privacy.It is crucial for public clouds to provide necessary services while protecting data privacy.Existing work on data privacy from the perspectives of privacy preserving computation was survied,integrity verification of public cloud computing results,public cloud data access control,and hardware secu-rity in cloud computing.Existing work is analyzed and future research directions for public cloud privacy is discussed.